ANALISIS BIBLIOMETRIK KEAMANAN PERUSAHAAN PENJUALAN ONLINE UNTUK MENCEGAH TERJADINYA KEJAHATAN SIBER - Rizky Adin Adriansyah; Aldof Faris Anugrah (Jurnal Sistem Informasi dan Informatika (Simika), 2024)
The present study conducts a comprehensive bibliometric analysis of the research landscape related to cybersecurity, cybercrime, and online sales companies. Utilizing Vosviewer, the analysis encompasses a wide array of publications, including authors, organizations, countries, keywords, and information sources. The primary objective is to identify the prominent trends, key contributors, and major research themes in the field. By shedding light on the evolving landscape of cybersecurity and cybercrime in the context of online sales companies, the study's goal is to provide helpful insights for researchers and practitioners. Furthermore, the analysis seeks to highlight the prevalence of cybercrime in online sales companies and explore the various dimensions of cybersecurity. The findings of this study are expected to not only contribute to the existing body of knowledge but also to guide future research endeavors and policy formulations in the domain of cybersecurity and cybercrime within online sales companies.